Hating one's family - taking one's cross, finding or losing one's life, insipid salt - Amon, Josef (Documenta Q, 2024)
This volume in the series Documenta Q is concerned with the reconstruction of the Q text behind Luke 14:26-27; 17:33; 14:34-35 par. Matt 10:37-39; 5:13. Q 14:26-27; 17:33; 14:34-35 is a difficult pericope to position in Q. It is also distinctive for its uncommon "double-doublets" with Mark. The International Q Project's presentation of the critical text, together with the exhaustive history of research on which it is based, will enhance research in the Sayings Gospel Q, the historical Jesus, and New Testament theology. Just prior to the bibliography at the conclusion of the volume, the resultant critical text of Q 14:26-27; 17:33; 14:34-35 is printed. This Greek text is followed by English, German, and French translations (Lukan chapter and verse numeration is used for convenience and convention).